Effectiveness and cost-effectiveness of a brief school-based group programme for parents of children at risk of ADHD: a cluster randomised controlled trial - Sayal, Kapil; Taylor, John A.; Valentine, Althea; Guo, Boliang; Sampson, Christopher James; Sellman, Edward; James, Marilyn; Hollis, Chris; Daley, David (Wiley, 2016)
Background NICE guidelines recommend a stepped care approach for the identification and management of children with, or at risk of, Attention-Deficit / Hyperactivity Disorder (ADHD). We investigated the effectiveness, cost-effectiveness and acceptability of a group parenting intervention programme (+/- a teacher session) for children at risk of ADHD.